IMPLEMENTASI PROGRAM BAPAK/BUNDA ASUH ANAK STUNTING (BAAS) DALAM PENURUNAN STUNTING DI KOTA PEKANBARU TAHUN 2024 - Anzella, Sinta; Wasillah, Asiah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
Stunting is a serious health issue that impacts the quality of human resources in Indonesia. In 2024, the national prevalence of stunting reached 19.8%, falling short of the 14% target. In Pekanbaru City, the stunting rate increased from 8.7% (2023) to 14.5% (2024), affecting a total of 281 children spread across 15 subdistricts. This situation occurred amidst the implementation of the Foster Parents for Stunted Children Program (BAAS), a collaborative initiative involving the government, the private sector, and Baznas to accelerate the reduction of stunting through interventions focused on ensuring adequate nutritional intake, improving parenting practices, and providing sanitation assistance. Interventions were carried out by providing a donation of Rp750,000 per month for six months. However, of the 164 at-risk children, only 88 had foster parents, and only 24 consistently provided assistance, while 34 did not distribute any assistance at all. This study aims to analyze the implementation of the BAAS Program in efforts to reduce stunting in Pekanbaru City in 2024 using Charles O. Jones’s theory (organization, interpretation, application). The approach used was descriptive qualitative research through in-depth interviews with 10 informants The results of the study indicate that the implementation of the BAAS Program has not yet been optimal. From an organizational perspective, cross-sectoral coordination remains weak and is not supported by government funding. In terms of interpretation, the understanding of foster parents and program beneficiaries is not yet uniform. In terms of implementation, there are four main factors: the lack of government funding, inconsistency among foster parents, ineffective distribution mechanisms, and low awareness and self-reliance among beneficiary families Keywords: Program Implementation, BAAS, Stunting